Hydrolysed Fish Peptide, Turmeric and Garlic Powder Supplementation to Reducing Vibrio Bacteria in Litopenaeus vannamei - Setiyaningsih, Lilik; Fitriadi, Ren; Kusuma, Baruna; Anjaini, Jefri; Sukardi, Purnama (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Vibriosis disease caused by Vibrio bacteria is one of the main challenges in vaname shrimp (Litopenaeus vannamei) farming, as it can cause high mortality rates and decreased productivity. This study aims to evaluate the effectiveness of a combination of natural immunostimulants in turmeric (Curcuma longa) and garlic (Allium sativum) combined with hydrolysis of fish peptides in suppressing Vibrio spp. bacterial populations in the hepatopancreas organs. The study was conducted for 30 days using a completely randomised design of four treatments and three replications. Treatment A (feed+turmeric75%+garlic25%+fish peptide hydrolysis2%), Treatment B (feed+turmeric50%+garlic50%+fish peptide hydrolysis2%), Treatment C (feed+turmeric25%+garlic75%+fish peptide hydrolysis2%), and Treatment K (feed without immunostimulant and fish peptide hydrolysis). Total Vibrio spp. bacteria were counted using the total plate count method on the hepatopancreas organ of the shrimp. The results showed that the immunostimulant combination of turmeric 75%, garlic 25%, and fish peptide hydrolysis 2% (treatment A) significantly reduced the total number of Vibrio spp. bacteria in the hepatopancreas to 2.45 ± 0.213 log CFU/ml compared to the control. The combination of turmeric and garlic immunostimulants and fish peptide hydrolysis has the potential to be an effective natural strategy in controlling vibriosis disease in shrimp farming.